NEW EMPLOYEE TEST SYSTEM AT PT. RAJASA MITRAMEDIA USING PHP PROGRAMMING. - Fitria Puji Utami. (Jurnal Sistem Informasi, 2006)
In a company that wants to increase productivity, require quality human resources. Therefore, a company needs a system of effective recruitment in order to get employees - employees who have a high potential and skills. At PT. MITRAMEDIA RAJASA employees receiving system not computerized. This will prevent or reduce the efficiency of recruitment process. Here the author tried to make the recruitment system has been computerized.